5-Fluorouracil targets histone acetyltransferases p300/CBP in the treatment of colorectal cancer. (1st August 2017) - Du, Changzheng; Huang, Dandan; Peng, Yifan; Yao, Yunfeng; Zhao, Ying; Yang, Yang; Wang, Haiying; Cao, Linlin; Zhu, Wei-Guo; Gu, Jin
Abstract: Although 5-fluorouracil (5-FU) is known to interfere with the synthesis of ribonucleic acid and deoxyribonucleic acid, the mechanism underlying its therapeutic efficacy in colorectal cancer (CRC) has not been fully elucidated. We aimed to investigate the influence of 5-FU on histone acetylation, a well-established anti-cancer target, to reveal novel pharmacological effects of 5-FU and their significance for CRC therapy. Results demonstrated that 5-FU induces global histone de-acetylation in multiple CRC cell lines. We identified that 5-FU reduces the binding ability of histone acetyltransferases p300 and CBP to chromatin, and induces their degradation through lysosome. Further work revealed that the degradation of p300/CBP induced by 5-FU was dependent on chaperone-mediated autophagy, mediated by heat-shock cognate protein 70 kDa (hsc70) and lysosomal-associated membrane protein 2A (LAMP2A). Moreover, the degradation of p300/CBP is relevant to cellular resistance to 5-FU, since blocking the degradation enhances 5-FU's cytotoxicity in CRC cells. From clinical data, we demonstrated that low expression of p300/CBP in CRC tissue was closely associated with poor clinical response to 5-FU based-chemotherapy, based on the analysis of 262 colorectal samples from the patients receiving 5-FU treatment: compared to cases with high expression of p300/CBP, those with low expression had lower long-term disease-free survival rate and increased early-progression. These results elucidate a novel pharmacological effect of 5-FU involving global histone de-acetylation by promoting the degradation of p300/CBP, and highlights p300 and CBP as promising predictors of chemo-sensitivity to 5-FU treatment. Highlights: A novel pharmacological effect of 5-FU involving global histone de-acetylation in colorectal cancer is illuminated. The histone de-acetylation induced by 5-FU results from the degradation of histone acetyltransferases p300/CBP via lysosome. Low-expression of p300/CBP in colorectal cancer tissue is closely associated with poor clinical response to 5-FU treatment.